PERSEPSI ORANGTUA TERHADAP PEMBERIAN GIZI MELALUI BEKAL MAKANAN SEHAT KELOMPOK B TK ALIZAH SURABAYA - Qori’ah, Maria; Octa Viana, Ria; Syamsudin, Moh. Anas; Andriyanto, Dicky (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
Food is an important requirement for growth and development as an intermediary for the intake of nutrients needed by the body. Parents' perceptions greatly determine the provision of nutritional intake to children. This study observed how parents' perceptions based on education level and income towards providing nutrition through healthy food supplies. The research method uses a qualitative approach with data collection techniques through interviews. Simple random sampling of 22 parents in Group B TK Alizah Surabaya. Data analysis techniques are described descriptively. The results showed that parents' perceptions based on their level of education were still low in fulfilling nutritional intake through healthy food supplies. It also shows the similarity of income-based perceptions of a lack of purchasing power for healthy food due to a lack of income.